In vitro Antidiabetic, Antioxidant and Antiglycation Activity of Ethanolic Leaf Extract of Gomphrena globosa (Linn.) - Sherif, Arsia Tarnam Yakoob (Asian Journal of Biological and Life Sciences)
G. globosa L. is an everlasting tropical annual plant reported to possess several biological activities for curing ailments such as arthritis, diabetes, asthma, bronchitis and also known to possess anti tussive, anti-oxidant, anti-asthmatic and anti-cancer activities. The amino group of protein and carbonyl group of reducing sugar undergoes a non-enzymatic protein glycation reaction that leads to major complications in Diabetic patients. Several antiglycation agents of natural or synthetic origin are there to inhibit protein glycation reaction. But due to its toxicity, antiglycation agents of plant origin are gaining importance as an effective strategy to minimize diabetic complications. The aim of this study was to evaluate the antidiabetic, antioxidant and antiglycation activity of ethanolic leaf extract of G. globosa. The ethanolic leaf extract exerted its antidiabetic effect by inhibiting the activity of α-amylase (p<0.05) resulting in the delayed digestion of the dietary carbohydrates and lowering the amount of glucose liberated. The highest scavenging was observed at 500 μg concentrations and the percent inhibition was found to be 50.80% for DPPH assay and 57.24% (p<0.05) for hydroxyl free radical scavenging assay. 25mM of glucose concentration showed the highest uptake of glucose. The glucose adsorption capacities of G. globosa ethanolic leaf extract was directly proportional to the glucose concentration in the medium resulting in significantly higher glucose adsorption. The effect of antiglycation activity of G. globosa ethanolic leaf extract was found to be increasing with increase in time. The inhibition of ethanolic leaf extract was found to be maximum (27.66%) at 72 hr, followed by 23.7% at 48 hr and 13.7% at 24 hr for fructation with ROS modification/UV/guanosine. This result indicates that ethanolic leaf extract of G. globosa possess significant activity at desirable concentration.
Keywords: Antidiabetic; Antiglycation; Antiglycation end product; Antioxidant; Ethanol; Gomphrena globosa; Guanosine; ROS